REGIONAL RISK ASSESSMENT OF HIGHLY PATHOGENIC AVIAN INFLUENZA IN THE BORDER OF INDONESIA AND MALAYSIA: A SOCIO ECONOMIC PERSPECTIVE - Ilham, Nyak; Iqbal, Muhammad (Universitas Sebelas Maret, 2015)
The result of the study shows that the extent of both active and passive surveillance was still low due to large coverage area and lack of report cases of Highly Pathogenic Avian Influenza (HPAI) from poultry farmers. The level of coordination among cross-border institutions was still relatively worst so that the illegal trade was still occurred in the checkpoints and other entry points along the cross-border line. The movement of poultry and poultry products was still risky since the traders tend to be actively visiting and catching the poultry in the sheds. There were some handicaps in line with local socio culture such as multi events festivity with high consume of chickens and cock fighting activity in some spotted areas. It is suggested that active surveillance system together with zoonotic campaign should be implemented in order to obtain the immediate data and information as well as to attract poultry farmers to provide reporting on the case of HPAI in the respected areas.